The Impact of External and Internal Factors on the Dairy Farmer’s Household Economics - J. Atmakusuma; B. M. Sinaga; N. Kusnadi; I. K. Kariyasa (Tropical Animal Science Journal, 2019)
Domestic milk production is currently only able to meet 20% of the total domestic demand of milk, but this opportunity has not been responded well by dairy farmers. The objectives of this study were: (1) to analyze the performance of dairy farmers and (2) to analyze the impact of external factors (concentrate feed and milk prices) and internal factor (marginal productivity of concentrate feed) on production, income, and household welfare of dairy farmers. The number of sample households was 97 cooperative-member farmers and 46 cooperative-nonmember farmers in Lembang, West Java. The analytical method used included descriptive analysis and household economic models in the form of simultaneous equations. The results of the study showed that the scale of small-scale business with the percentage of lactating cattle and dairy farmers’ productivity was still low. When the price of concentrate feed rises, the impact of the policy of increasing milk prices is greater than the increase in the marginal productivity of concentrate feed on increasing business income and household welfare of dairy farmers.